Clausewitz's puzzle the political theory of war - Herberg-Rothe, Andreas (Oxford University Press, 2007)
Blending detailed contextual analysis with issues in modern-day international relations this book provides a major new analysis of the theory of Clausewitz and its relevance to contemporary society. This book argues that Clausewitz developed a wide-ranging political theory of war by reflecting on the success, the limitations, and the failure of Napoleon's method of waging war, a theory, which is still relevant in light of contemporary conflict. This new interpretation is the result of reflecting on Clausewitz's theory in light of the new developments and lays down the foundation of a general theory of war by concentrating on Clausewitz's historical analyses of war campaigns. For the first time analysis of three paradigmatic military campaigns is placed at the centre of understanding surrounding Clausewitz's 'On War'. The author argues that the limitations of Napoleon's strategy, as revealed in Russia and in his final defeat, enabled Clausewitz to develop a general theory of war.